Preparation, characterization and adsorption performance of the koh-activated carbons derived from kenaf fiber for lead (II) removal from waste water - Chowdhury, Z.Z.; Ashraf, M.A.; Khan, R.A.; Zain, Sharifuddin Md (2011)
In this study, activated carbon was prepared from kenaf fiber (KF) by using physiochemical activation method consisting of potassium hydroxide (KOH) impregnation with carbon dioxide (CO 2) gasification. Pore structure and physical characteristics of the prepared activated carbon were determined. Adsorption studies for divalent lead (Pb) were carried out to delineate the effect of contact time, temperature, pH and initial metal ion concentration. About 93.23% of Pb (II) was removed from 100 mg/l solution at pH 5.5. The experimental data followed pseudo second order kinetics which confirms chemisorptions. The linear plots of intra particle diffusion demonstrated that, the adsorption process is mainly governed by pore diffusion. The values of Langmuir dimensionless constant, R L and Freundlich constant, 1/n were less than 1 representing favorable process for adsorption. Thermodynamic parameters such as ΔG°, ΔH° and ΔS° which are related to Gibbs free energy, enthalpy and entropy were evaluated. The research concluded that activated carbon from kenaf fiber (KFAC) has sufficient porosities and surface area and it has got good potential to remove Pb (II) from waste water. © 2011 Academic Journals.